2015
DOI: 10.1007/s10661-015-4818-6
|View full text |Cite
|
Sign up to set email alerts
|

Studies of pesticide residues in tomatoes and cucumbers from Kazakhstan and the associated health risks

Abstract: The aim of the present study was to assess the level of pesticide residues in vegetables in the Almaty Region of Kazakhstan and to determine the potential health risks associated with the exposures to these pesticides. A total of 82 samples of cucumbers and tomatoes from top agro-based market and greenhouses were analysed using a gas chromatography–micro electron capture detector/nitrogen–phosphorous detector (GC-μECD/NPD), a multiresidue method to analyse 184 different pesticide types. The results indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
43
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(61 citation statements)
references
References 31 publications
9
43
0
2
Order By: Relevance
“…This is consistent with previous studies in which pesticides were detected in a whole food basket including yam at concentrations below the MRLs (Adeyeye and Osibanjo 1999;Asiedu 2013;Bempah and Donkor 2011;Kolani et al 2016;Yang et al 2016). Other studies show similar results (Blasco et al 2006;Lozowicka et al 2015;Osibanjo and Adeyeye 1995;Su et al 2003).…”
Section: Pesticides Residues In Yam Samplessupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with previous studies in which pesticides were detected in a whole food basket including yam at concentrations below the MRLs (Adeyeye and Osibanjo 1999;Asiedu 2013;Bempah and Donkor 2011;Kolani et al 2016;Yang et al 2016). Other studies show similar results (Blasco et al 2006;Lozowicka et al 2015;Osibanjo and Adeyeye 1995;Su et al 2003).…”
Section: Pesticides Residues In Yam Samplessupporting
confidence: 92%
“…The recovery studies revealed that the QuEChERS method is an efficient method for multi-residue analysis of the tested pesticides in yam. The recoveries of all the 25 pesticides analyzed were well within the 70% -120% performance criteria (Bempah and Donkor 2011;Berrada et al 2010;Gilbert-López et al 2010;Lesueur et al 2008;Lozowicka et al 2015;Mekonen et al 2014;Nguyen et al 2008;Osman et al 2010) These recoveries indicate that the method used is reproducible. In terms of accuracy and precision i.e.…”
mentioning
confidence: 52%
“…Tomatoes are sensitive to pests hence require multiple use of pesticides which can be found as residues if not properly used. In Kazakhstan, Lozowicka et al (2015) detected up to nine pesticide residues including azoxystrobin, metalaxyl, flusilazole and triadimefon. Multiple contamination increases health risks as there could be a possibility of synergism in their effects.…”
Section: Multiple Pesticide Residue Levelsmentioning
confidence: 99%
“…The incidence of pesticide residues in the tested vegetables may be due to vegetable crops being damaged by many pests and their various species [17,18] (Table 4); therefore, different pesticides are applied to protect these crops against pests and diseases, particularly vegetable crops that are cultivated under greenhouse conditions [19,20]. The humid conditions and large amount of food in greenhouse environments make them ideal habitats for pests and make crops in these environments more susceptible to pests such that successive applications of pesticide treatments are required to prevent considerable crop losses [21,22]. The highest concentrations of detected pesticides were recorded for the fungicide cyproconazole (in chili pepper), followed by the insecticide profenofos (in cabbage), the fungicide myclobutanil (in cucumber), the fungicide metalaxyl (in tomato), and the insecticide methomyl (in eggplant).…”
Section: Discussionmentioning
confidence: 99%